Increasing health degree by implementing health checks for residents of Silaberanti Village - Bastian Bastian; Anggun Sagita; Firna Kamilatun Nuha; Dilla Wulandari; Cyndy Hasendra; Andini Junytri; Anisa Nur Afifa; Novi Rianti; Depi Anggraini; Ayu Enjellya Prisicilya; Redy Novrian Utama (Universitas Muhammadiyah Magelang, 2024)
The success of health development includes increasing public awareness and willingness to adopt healthy behaviors. In line with this, this community service activity aims to improve people's understanding of their personal health conditions and awareness of the importance of health screening or medical check-ups. Health examinations were conducted in RT 31 and RT 32 of Silaberanti Village. The methods used were cholesterol, uric acid, blood pressure, blood type, and height and weight checks. After the checks, it was found that 98% of participants had normal uric acid levels, 67% had high cholesterol levels, and 41% had high blood pressure above 140/90. The feeling experienced by the community after the health check was an increased awareness of their health conditions, so that if there were any health problems, they could be detected as soon as possible and treated as soon as possible.